Greenwashing and the mith of sustainability in fashion: alienation and commodity fetishism (Revista de Ensino em Artes, Moda e Design, 2022)
The sustainability myth, along with greenwashing, are alienation tools used by the market in order to divert attention from the problems caused by the capitalist mode of production. The approach of the theme in this article reveals the contradictions inherent to the current socioeconomic form, especially in reference of the fashion spectrum, through the articulation of the concepts of commodity fetishism, alienation, use value and metabolic rift. As objective, is sought the intersection of discourses around sustainability in fashion through a socio-political approach in bibliographic review of theoretical specialists that help to demystify the capitalist mode of production. As result of the research, it is possible to demonstrate the insufficiency and contradictions of the narratives carried out by the fashion market, and the capitalist system in general, also identifying greenwashing practices in addition to the use of the sustainability myth as an instrument for validating predatory practices of capitalism as well in reference of the environment as the society.
Keywords: greenwashing; sustainability myth; commodity fetishism